Experimental study of admixture on Bentonite clay reinforced concrete as a partial substitute to cement - Ahmed, Siraj; Kunte, Anil; Roy, Aashis (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The mortar mixtures were prepared in various proportioned with cement to sand ratio of 1:3 and 1:4. The reinforced concretes were cast for the same flow level but different percentages of clay (0, 5, 10 & 15%) dosage. The prepared motor concrete subjected for structural study and mechanical property analysis. In FTIR spectra shows predominant peaks are observed the presence of admixture and clay in the concrete motor. The XRD spectra indicates the formation tetrahedrally arrangement of silicate and octahedrally arrangement of aluminate groups in clay mixed concrete. The surface morphology significantly improved upon adding of different admixture as examined in SEM image. The mechanical study revealed that the compressive strength increases with increase in clay percentages up to C-2 (10 wt %) due to the strong adhesion because of mixture of water reduce and water repellent which makes better compact and reduce porosity. The addition of slump flow improved due to presence of polycarboxylate ether and the evident workability loss started after the resting time of 25 min.